PV-Based Water Pumping System Without Storage Battery - Rai, Astha; Dongol, Kapka; Dhungana, Sandesh; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2023)
The in rural area, where there is no electricity supply from the grid, PV-based water pumping system is Very popular. The conventional PV-based water pumping system stores electrical energy generated by solar panel in the storage battery. A DC to AC inverter is used to drive the water pump coupled with conventional AC motor. The efficiency of this type of water-pump system low due to the power losses during charging and discharging process and life of the very is very short. In this paper a stand-alone Photovoltaic (PV) systems is presented for water pumping without using storage battery which can be used for irrigation and drinking water. The proposed systems without battery can provide a cost-effective use of solar energy. Simulation model of the proposed scheme is developed and proto-type hardware is fabricated. The simulation results and hardware results shows the technical feasibility of the proposed scheme.